2012
DOI: 10.1108/14637151211215019
|View full text |Cite
|
Sign up to set email alerts
|

Achieving supply chain integration using RFID technology

Abstract: PurposeDespite the high operational and strategic potentials of radio frequency identification (RFID) technology, very few studies have been conducted about its role as enabler of supply chain integration to achieve high‐level operational efficiency. The purpose of this paper, therefore, is to be an initial effort towards bridging the existing knowledge gap in the literature.Design/methodology/approachThis exploratory research was conducted in one retail supply chain. A multi‐method approach combining a longit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…In previous studies of specialists, numerous benefits related to SCM information technology (IT) optimization have been identified, such as (1) the exchange of information between SC stakeholders [57][58][59][60]; (2) the transformation of intra-and inter-organizational business processes (cancellation, redesign, automation) [61][62][63], operational efficiency [64] and revenue growth [59], profitability, and improvement of stakeholder relations [65,66]; and (3) improving relational and contractual governance by effectively mitigating the opportunism of partners [67]. In addition, BDA could also generate future opportunities for stakeholders such as obtaining a competitive advantage [68] and reducing exposure to fraud or other malfunctions [69,70].…”
Section: Benefits and Constraints Of Bda For Scmmentioning
confidence: 99%
“…In previous studies of specialists, numerous benefits related to SCM information technology (IT) optimization have been identified, such as (1) the exchange of information between SC stakeholders [57][58][59][60]; (2) the transformation of intra-and inter-organizational business processes (cancellation, redesign, automation) [61][62][63], operational efficiency [64] and revenue growth [59], profitability, and improvement of stakeholder relations [65,66]; and (3) improving relational and contractual governance by effectively mitigating the opportunism of partners [67]. In addition, BDA could also generate future opportunities for stakeholders such as obtaining a competitive advantage [68] and reducing exposure to fraud or other malfunctions [69,70].…”
Section: Benefits and Constraints Of Bda For Scmmentioning
confidence: 99%
“…The AMQP protocol was used due to its ability to support a request/response architecture and also a publish/subscribe architecture [22]. Compared to other protocols such as MQTT, HTTP, or CoAP, AMQP offers a more secure communication protocol [23]. AMQP employs various approaches to TLS negotiation as well as a single port TLS model, Pure TLS and WebSocket tunnel TLS [23].…”
Section: Gateway Nodementioning
confidence: 99%
“…Compared to other protocols such as MQTT, HTTP, or CoAP, AMQP offers a more secure communication protocol [23]. AMQP employs various approaches to TLS negotiation as well as a single port TLS model, Pure TLS and WebSocket tunnel TLS [23]. Because of the wide range and variety of messaging services, AMQP has been chosen as a business standard [24].…”
Section: Gateway Nodementioning
confidence: 99%
“…Liu et al, 2012;Maçada et al, 2013;Machikita & Ueki, 2013;Mentzas et al, 2006;Paulraj et al, 2008;Zhang et al, 2012); inventory management (Zhu, Mukhopadhyay & Kurata, 2012); logistics management (Norbis, Meixell & Tuggle, 2013;Rollins, Pekkarinen & Mehtälä, 2011;Viswanadham & Gaonkar, 2009) Eng Wadhwa & Saxena, 2007;Yang, 2012); SC collaboration (Braziotis & Tannock, 2011;Corso et al, 2010;Eng, 2006;Wadhwa & Saxena, 2007;Yang, 2012a); SC integration (Chen et al, 2013;Lin, 2014;Liu et al, 2013a;Nagati & Rebolledo, 2013;Shunk et al, 2007;Singh & Power, 2014;Wamba, 2012;Xiuhong, 2013;Zhang & Huo, 2013); SC interoperability (Whitman & Panetto, 2006); SC learning (Biotto, De Toni & Nonino, 2012;Tennant & Fernie, 2013) cross-functional coordination, product innovation, global manufacturing reach), KM enablers (i.e., knowledge sharing, knowledge development, internal innovation climate, culture of competitiveness, power, IT infrastructure, dependence and trust, e-business applications, networked sources of knowledge, inter-organizational communication) and performance at the SC level or firm level; (ii) SC practices and KM capabilities (i.e., socialization mechanisms and technological innovation capabilities, innovation capabilities, extraction of specific knowledge patterns, supplier relationship management capability, learning capabilities); (iii) KM strategies; and (iv) test and validate conceptual frameworks. Findings also show that conceptual models hold credibility among the qualitative research methods notice by the authors.…”
Section: Exploitationmentioning
confidence: 99%
“…Through a case study in a retail SC, Wamba (2012) Singh and Power (2014) showed the potential to build innovative capability via integration through collaboration for the purpose of accessing, sharing and leveraging knowledge. Xiuhong (2013) proposed a system dynamics model of knowledge transfer as the ability to knowledge integration and expressive power.…”
Section: Supply Chain Integrationmentioning
confidence: 99%